Cathode unit and method for manufacturing the cathode unit

The cathode unit for solid-state batteries, utilizing a composite material with less than one weight percent fibrillated PTFE as a binder, addresses the challenges of high resistance and processing issues in existing technologies, achieving improved electrical and ionic performance.

JP2025060916APending Publication Date: 2025-04-10FRAUNHOFER GESELLSCHAFT ZUR FORDERUNG DER ANGEWANDTEN FORSCHUNG EV +1
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
JP2024231176
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2018-12-18
Filing Date
2024-12-26
Publication Date
2025-04-10

AI Technical Summary

Technical Problem

Existing solid-state battery technologies face challenges in achieving low electrical and ionic resistance, particularly due to high binder content and processing issues with solid electrolyte materials.

Method used

A cathode unit for solid-state batteries is manufactured using a composite material with a binder content of less than one weight percent, specifically fibrillated polytetrafluoroethylene (PTFE), which reduces electrical and ionic resistance and facilitates easier processing.

Benefits of technology

The use of fibrillated PTFE as a binder in the cathode unit reduces the amount of binder required, improving electrical properties and enabling easier processing and application, thereby achieving lower electrical and ionic resistance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025060916000001_ABST
    Figure 2025060916000001_ABST
Patent Text Reader

Abstract

To provide a cathode unit having electric resistance and ionic resistance as low as possible, and a method for manufacturing the cathode unit on a large scale.SOLUTION: A cathode unit has a layer composed of a composite material having an electrode material, a solid electrolyte material, a conductive additive, and polytetrafluoroethylene as a binder. The composite material contains less than 1 wt.% of polytetrafluoroethylene, and the polytetrafluoroethylene is at least partially present as fibrillated polytetrafluoroethylene.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a cathode unit and a method for manufacturing the cathode unit. [Background technology]

[0002] Solid-state batteries are a very promising further development of lithium-ion batteries. In solid-state batteries, instead of a liquid electrolyte system, a lithium-ion conductor (or a sodium-ion conductor) existing as a solid is used as the electrolyte. It simultaneously acts as an ion conductor between the active material particles and as an ion-conducting separator between the anode and the cathode. Important here is the possibility of large-scale processing of the powdered electrode mixture and the possibility of forming an intimate contact surface between the solid electrolyte and the active material with as many contact points as possible and as few hollow spaces as possible.

[0003] Solid-state batteries can be classified in particular with regard to the type of electrolyte used (oxide-based, sulfide-based, polymer-based). Oxide solid electrolytes have high chemical and mechanical stability. However, processing into non-porous thin electrodes or solid electrolyte membranes is a major challenge due to the high sintering temperatures. Sulfide electrolyte materials are also rarely deposited over large areas. Different binder-solvent mixtures are used for the anode, cathode and electrolyte layers for application by wet chemical processes, as described for example in US 2016 / 248120 A1, because otherwise the application of a layer may cause solvation of the layers below. A relatively high binder content of a few percent by weight or mass, and the higher electrical and ionic resistance resulting therefrom, are disadvantageous in such processes. Summary of the Invention [Problem to be solved by the invention]

[0004] SUMMARY OF THE PRESENT DISCLOSURE An object of the present invention is to provide a cathode unit and a method for producing the same that overcome the above-mentioned drawbacks and enable large-scale production of cathode units with as low electrical resistance and ionic resistance as possible. [Means for solving the problem]

[0005] This object is achieved by a cathode unit according to claim 1 and a method for producing a cathode unit according to claim 11. Advantageous embodiments and further developments are set out in the dependent claims.

[0006] A cathode unit for a solid-state battery, preferably an alkali-ion solid-state battery or a lithium or sodium battery, has a layer of a composite material. The composite material has an electrode material, a solid electrolyte material, a conductive additive, and polytetrafluoroethylene (PTFE) as a binder. The composite material has less than 1 weight percent polytetrafluoroethylene, and the polytetrafluoroethylene is at least partially present as fibrillated polytetrafluoroethylene.

[0007] The use of fibrillated polytetrafluoroethylene as a binder allows for reduced binder usage, requiring only small amounts of polytetrafluoroethylene, less than 1 weight percent of the cathode unit, and improves electrical properties. The composite materials are typically solvent-free, allowing for easier processing and easier application and formation of free-standing films.

[0008] The cathode unit may have a current collector made of a conductive material to which a layer of the composite material is applied. Here, the term "conductive" refers to a current collector having a conductivity of 10 at room temperature, i.e., 25° C. 5 It should be understood as any material having a conductivity of more than S / m. Alternatively or additionally, the layers of the composite material may be electrically conductive in that they are typically selected to correspond to a high proportion of electrically conductive additive that is also electrically conductive.

[0009] The polytetrafluoroethylene in the composite can be present as at least partially uniaxially and / or biaxially oriented polytetrafluoroethylene to set the desired mechanical properties. Of course, the polytetrafluoroethylene can also be present as fully uniaxially or fully biaxially oriented or aligned polytetrafluoroethylene.

[0010] The composite material may contain between 60 and 99 weight percent of the electrode material, preferably 100 weight percent. The composite material typically contains at least 0.1 weight percent polytetrafluoroethylene, provided sufficient binder is available. The composite material preferably contains less than 0.5 weight percent polytetrafluoroethylene, with 0.1 to 0.4 weight percent being particularly preferred.

[0011] The electrode material can include, for example, sulfur, lithium sulfide (Li2S), lithium metal oxide, sodium metal oxide, or mixtures thereof to form a sulfide cathode. In particular, the conductive electrode material can be a transition metal oxide, preferably LiCoO2, LiNiO2, LiNi1_ x Co x O2, LiFePO4, LiMnO2, LiMn2O4, Li2Mn3NiO8, LiNi x Co y Mn z O2, LiNi x Co y Al z O2 (where x+y+z=1), Li4Ti5O 12 , Li2FeSiO4 or mixtures thereof. The corresponding analogues containing sodium, preferably Na2S, Na xMnO2, Na3V2(PO4)3, NaFePO4, Na2FePO4F, NaNiMnO2, Na2TiO7 and / or NaTi2(PO4)3 can equally be used. As electrode material it is also possible to use multilayer oxides of the AMO2 type, where A=Li, Na, M=Co, Mn, Ni. Said different materials can also generally be combined with each other to form the electrode.

[0012] Solid electrolyte materials include Li2S-P2S5, Li2S-GeS2, Li2S-B2S3Li2S-SiS2, Li5PS6CI, Li2S-P2S5-LiX (X=CI, Br, I), Li2S-P2S5-Li2O, Li2S-P2 S5-Li2O-Lil, Li2S-SiS2-Lil, Li2S-SiS2-LiBr, Li2S-SiS2-LiCI, Li2S-SiS2-B2S3-Lil, Li2S-SiS2-P2S5-Lil, Li2S-P2S5-Z m S n (wherein m and n are integers and M is selected from P, Si or Ge), Li2S-SiS2-Li3PO4, Li2S-SiS2-Li p MO q , (where p and q are integers and M is selected from P, Si or Ge), Na2S-P2S5, Na2S-GeS2, Na2S-B2S3, Na6PS5CI, Na2S-SiS2, Na2S-P2S5-NaX (X=CI, Br, I), Na2S-P2S5-Na2O, Na2S-P2S5-Na2O-Nal, Na2S-SiS2-Nal, Na2S-SiS2-NaBr, Na2S-SiS2-NaCI, Na2S-SiS2-B2S3-Nal, Na2S-SiS2-P2S5-Nal, Na2S-P2S5-Z m S n (wherein m and n are integers and M is selected from P, Si or Ge), Na2S-SiS2-Na3PO4, Na2S-SiS2-Na p MO q(where p and q are integers and M is selected from P, Si or Ge), or a material consisting of these mixtures. Lithium may generally be substituted with sodium in all compounds named in this application. The solid electrolyte material is typically present in the powder mixture between 1 weight percent and 35 weight percent. Carbon nanotubes, black carbon, graphite, graphene and / or carbon nanofibers may be included in the composite as conductive additives in the range of 1 weight percent to 5 weight percent. The solid electrolyte material is typically an electrochemically active material. The conductive additive may be an electrochemically inactive material.

[0013] The electrode material may include a protective layer applied to the particles of this material. This protective layer should prevent side reactions between the solid electrolyte material and the electrode material. The protective layer may include, for example, Li2O-ZrO2 or other metal oxides. All particles of the electrode material may have a protective layer, typically with a thickness of 2-5 nm.

[0014] The conductive current collector usually comprises or is completely made of a conductive material, preferably aluminum. Alternatively or additionally, the current collector may be formed as a current collector layer, in particular a flat current collector with a preferably double-sided coating, as a metal foam or as a current collector layer formed as a foam, a fiber fabric, a non-crimped fiber or a primer layer. Here, the primer layer may likewise be flat.

[0015] The method for producing a cathode unit for a solid-state battery according to the invention is characterized in that a powder mixture is produced from an electrode material, a solid electrolyte material, a conductive additive, and polytetrafluoroethylene as a binder, the powder mixture having a proportion of polytetrafluoroethylene of less than 1 weight percent. At least partially fibrillated polytetrafluoroethylene is formed in the powder mixture by the action of a shear force on the powder mixture. The powder mixture is then formed into a flexible composite layer. The flexible composite layer is preferably applied to a conductive current collector to form the cathode unit. Means may also be provided for subsequent compaction of the flexible composite layer and / or the current collector.

[0016] A simple processing is ensured by the powder mixture, which should be understood as a material that exists in granular form and is composed of a plurality of small particles with a size of up to 15 μm, or is a granular or fragmentary mixture or bulk material. The powder mixture can be present in dry form to simplify handling. In addition, the powder mixture is also not pourable in the sense of the DIN EN ISO 6186 standard. "Dry" should be understood within the framework of this document such that the components of the powder mixture are present as a solid, without any material present in a liquid or liquid aggregate state. This powder mixture is solvent-free and can be collected without solvent. A "flexible composite layer" should be understood as a composite layer that can be bent or folded or unfolded up to 180° at room temperature without destruction. The bending radius is in particular between 90 μm and 100 μm, particularly preferably 100 μm.

[0017] The formation of at least partially fibrillated polytetrafluoroethylene can be carried out by grinding, mixing with a worm shaft or calendar rolling device, kneading device, pestle device, or a combination of these methods to ensure efficient fibrillation.The formation of at least partially fibrillated polytetrafluoroethylene is typically carried out at room temperature.However, in order to reach a binder content of less than 0.5 weight percent, the formation is preferably carried out at an elevated temperature of 60°C to 100°C, particularly preferably 90°C to 100°C, and particularly preferably 100°C.However, polytetrafluoroethylene can also be present in a fully fibrillated form.

[0018] Forming the powder mixture into a flexible composite layer is typically done by rolling, pressing, or extrusion, although a combination of the above methods can also be used.

[0019] Application of the flexible composite layer to the conductive current collector layer is typically carried out at a temperature of from 60°C to 120°C, preferably from 80°C to 100°C.

[0020] The described methods can be used to manufacture the described cathodes, i.e. the described cathodes can be manufactured by the described methods.

[0021] The solid-state or lithium battery according to the present invention comprises a cathode unit having the above-mentioned properties.

[0022] An embodiment of the invention is illustrated in the drawings and will now be described with reference to FIGS.

[0023] The following is shown: [Brief description of the drawings]

[0024] [Figure 1] FIG. [Diagram 2] FIG. 2 shows a cathode having a solid electrolyte membrane corresponding to FIG. 1. [Diagram 3] FIG. 2 shows a cathode with a solid electrolyte membrane and an anode corresponding to FIG. 1. [Figure 4] Scanning electron micrograph of a dried composite film. [Diagram 5] FIG. 14 shows the discharge voltage profile of a test cell having 0 weight percent binder content. [Figure 6] FIG. 6 shows the discharge voltage profile of a test cell having a binder content of 0.1 weight percent corresponding to FIG. 5. [Figure 7] FIG. 6 shows the discharge voltage profile of a test cell having a binder content of 0.3 weight percent corresponding to FIG. 5. [Figure 8] FIG. 6 shows the discharge voltage profile of a test cell having a binder content of 0.7 weight percent corresponding to FIG. 5. [Figure 9] FIG. 6 shows the discharge voltage profile of a test cell having a binder content of 1 weight percent corresponding to FIG. 5. [Figure 10] Nyquist plot of the internal resistance of the test cell. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0025] A conductive current collector layer 1 made of aluminum as a substrate or carrier film with a first electrode 2 forming a cathode unit is shown in a schematic side view in FIG. 1. The first electrode 2 is formed in this embodiment of a powdered composite material. This composite material has 85 weight percent of lithium nickel manganese cobalt (NCM), 13 weight percent of a solid electrolyte material such as lithium Li2S-P2S5, 2 weight percent of conductive carbon nanotubes as conductive additives and 0.1 weight percent of polytetrafluoroethylene as binder. The binder content here is related to the total mass with a ratio of NCM:C:SE of 85::2:13 (SE should be marked as its abbreviation for solid electrolyte). The obtained composite material is in powder form, dry and solvent-free, but not for pouring. This composite material can be mixed into a mortar. In this process, shear forces act on the mixture or powder mixture forming the composite material, forming fibrils along the force vector. In the next step, the composite is rolled onto a plate with a roller to the desired layer thickness and laminated onto a carrier film 1, which has a thickness of less than 20 μm and may be provided with a carbon primer. The final shaping of the cathode unit is done by stamping or laser cutting.

[0026] The composite material can alternatively be added directly to the calender gap as a powder mixture or bulk material without solvent additives. As described in German patent application DE 10 2017 208 220, different rotation speeds of the two calender rollers are used, for example in a ratio of 10:9 to 10:4. A ratio of rotation speeds of 2:1, for example 10 mm / s:5 mm / s or 20 mm / s to 10 mm / s, is advantageous. This causes shear forces to act on the composite material in the gap, leading to the formation of fibrils along the direction of the roller travel. A layer formation occurs on the rapidly rotating roller. In the next step, the layer is laminated on the substrate film 1 and the final shaping is carried out by stamping or laser cutting. Furthermore, the formation of the film in the calender gap already allows a large compression of the layers involved during film formation. Of importance for this is the particle size distribution of the powders used for the composite, which must be coordinated with one another in order to fill the gaps of the larger particles as efficiently as possible with the smaller particles and to keep the porosity low. Therefore, the density before pressing is 1.7 - 1.9 g / cm 3 This corresponds to a porosity of 50 to 55 percent. The pressed density is typically 3.5 g / cm 3 and the porosity approaches the ideal porosity of 0 percent for values ​​up to 10 percent.

[0027] The treatment is advantageously carried out at elevated temperatures between 60°C and 100°C, so that the required binding agent or binder content is considerably reduced. The cathode unit thus obtained has a layer sequence: substrate membrane 1 - first electrode 2. The first electrode 2 typically has a structure in its composition of 60 to 99 weight percent of cathode material, 13 to 35 weight percent of solid electrolyte material, 2 to 5 weight percent of conductive additive, the binder (polytetrafluoroethylene) making up 0.1 to 1 weight percent of the total mass. The pressing mentioned above is typically carried out as the final process step. This is carried out at a pressure of 290 MPa to 450 MPa, preferably 300 MPa, to ensure the fluidity of the electrolyte. All processing steps involving the solid electrolyte material are preferably carried out under a protective gas, for example a noble gas, preferably argon, or nitrogen, or dry air with a dew point below -50°C.

[0028] In figure 2 a cathode unit of a carrier membrane 1 and a first electrode 2 is shown in a view corresponding to figure 1, in which a solid electrolyte membrane 3 is arranged in direct contact, i.e. without any space between them, with the opposite side or surface of the first electrode 2 to which the carrier membrane 1 as current collector layer is attached in direct contact. The carrier membrane 1 and the first electrode 2 are of identical size except for the thickness and are arranged in alignment with each other, but the solid electrolyte membrane 3 is wider than the first electrode 2. Repeating elements are given the same reference numbers in this and the following figures.

[0029] FIG. 3 shows a solid-state battery in which, in addition to the structure shown in FIG. 2, an anode unit is attached to a side disposed opposite to one side of the solid electrolyte membrane 3 in a view corresponding to FIG. 1 and FIG. 2. The anode unit is formed by directly contacting the second electrode 4 and the second substrate membrane 5 as a second current collecting layer with each other. The second electrode 4 is in direct contact with the solid electrolyte membrane. The solid electrolyte membrane, the second electrode 4 and the second carrier membrane 5 are aligned with each other so that the thickness of the second carrier membrane 5 is the thinnest, the thickness of the second electrode 4 is the thickest, and the thickness of the solid electrolyte membrane 3 is between the thickness of the second electrode 4 and the thickness of the second carrier membrane 5. The capacitance is typically adjusted with respect to each other, from which the thickness arises. The first electrode can have a thickness of, for example, 100 μm, and the second electrode is a lithium anode with a thickness of, for example, up to 10 μm. It is also possible to make the thickness of the first carrier membrane 1 and the second carrier membrane 5 the same. The thickness of the first electrode 2 is thicker than the thickness of the solid electrolyte membrane 3 and thicker than the thickness of the first carrier membrane 1. Battery electrodes for primary and secondary batteries can be fabricated using the methods described above with layers of moisture or solvent sensitive materials, preferably lithium or sodium ion compounds, solid state supercapacitor electrodes, or any kind of sulfide electrolyte.

[0030] Figure 4 shows a scanning electron micrograph (SEM) of a dried membrane consisting of NCM solid electrolyte (SE), carbon fiber (CNF) in a mass ratio of 85:13:2, and 0.3 weight percent of the total mass being polytetrafluoroethylene (PTFE).

[0031] Figures 5 to 9 show the discharge voltage profiles of the test cells of the above-described solid-state battery, where each voltage is input onto a capacitance. The percentage of polytetrafluoroethylene is 0 weight percent in Figure 5; 0.1 weight percent in Figure 6; 0.3 weight percent in Figure 7; 0.7 weight percent in Figure 8; and 1 weight percent in Figure 10.

[0032] In Figure 10, impedance measurements are shown in a Nyquist plot, where the imaginary part is input over the real part. The measurement curves show test cells with binder at percentages of 0.1, 0.3 and 1 weight percent. The internal resistance of each solid-state battery increases as the percentage of polytetrafluoroethylene increases.

[0033] The embodiments disclosed by way of example only may be combined with each other and may be claimed separately.

Claims

1. A cathode unit for a solid-state battery having a layer of a composite material having an electrode material, a solid electrolyte material, a conductive additive, and polytetrafluoroethylene as a binder, the composite material comprises less than 1 weight percent polytetrafluoroethylene; and The polytetrafluoroethylene is at least partially present as fibrillated polytetrafluoroethylene, Cathode unit.

2. The composite material is characterized in that it contains 60 weight percent to 99 weight percent of the conductive electrode material. The cathode unit according to claim 1 .

3. The electrode material is LiCoO 2 , LiNiO 2 , LiNi 1 _ x Co x O 2 , LiFePO 4 , LiMnO 2 , LiMn 2 O 4 , Li 2 Mn 3 NiO 8 , LiNi x Co y Mn z O 2 , LiNi x Co y Al z O 2 (where x+y+z=1), Li 4 Ti 5 O 12 , Li 2 FeSiO 4 , Na 2 S, Na x MnO 2 , Na 3 V 2 (PO 4 ) 3 , NaFePO 4 , Na 2 FePO 4 F, NaNiMnO 2 , Na 2 TiO 7 and / or Na-Ti 2 (PO 4 ) 3 or a mixture thereof, The cathode unit according to claim 1 or 2.

4. The solid electrolyte material is Li 2 SP 2 S 5 , Li 2 S-GeS 2 , Li 2 S.B. 2 S 3 , Li 6 P.S. 5 C.I., Li 2 S-SiS 2 , Li 2 SP 2 S 5 -LiX (X=CI, Br, I), Li 2 SP 2 S 5 -Li 2 O, Li 2 SP 2 S 5 -Li 2 O-Lil, Li 2 S-SiS 2 -Lil, Li 2 S-SiS 2 -LiBr, Li 2 S-SiS 2 -LiCI, Li 2 S-SiS 2 -B 2 S 3 -Lil, Li 2 S-SiS 2 -P 2 S 5 -Lil, Li 2 SP 2 S 5 -Z m S n (wherein m and n are integers and M is selected from P, Si or Ge), Li 2 S-SiS 2 -Li 3 PO 4 , Li 2 S-SiS 2 -Li p MO q (wherein p and q are integers and M is selected from P, Si or Ge), Na 2 SP 2 S 5 , Na 2 S-GeS 2 , Na 2 S.B. 2 S 3 , Na 6 P.S. 5 CI, Na 2 S-SiS 2 , Na 2 SP 2 S 5 -NaX (X=CI, Br, I), Na 2 SP 2 S 5 -Na 2 O, Na 2 SP 2 S 5 -Na 2 O-Nal, Na 2 S-SiS 2 -Nal, Na 2 S-SiS 2 -NaBr, Na 2 S-SiS 2 -NaCI, Na 2 S-SiS 2 -B 2 S 3 -Nal, Na 2 S-SiS 2 -P 2 S 5 -Nal, Na 2 SP 2 S 5 -Z m S n (wherein m and n are integers and M is selected from P, Si or Ge), Na 2 S-SiS 2 -Na 3 PO 4 , Na 2 S-SiS 2 -Na p MO q (wherein p and q are integers and M is selected from P, Si or Ge) or a mixture thereof, A cathode unit according to any one of claims 1 to 3.

5. The current collector comprises or is made of aluminum and / or is preferably formed as a current collector layer having a double-sided coating, a metal foam, a woven fabric or a current collector layer provided with a primer layer, A cathode unit according to any one of claims 1 to 4.

6. The composite material is characterized in that it is solvent-free. A cathode unit according to any one of claims 1 to 5.

7. The polytetrafluoroethylene is characterized in that it exists as fully uniaxially or fully biaxially oriented polytetrafluoroethylene. A cathode unit according to any one of claims 1 to 6.

8. The electrode material includes a protective layer applied to particles of the electrode material. A cathode unit according to any one of claims 1 to 7.

9. The protective layer is Li 2 O-ZrO 2 Characterized in that it comprises The cathode unit according to claim 8.

10. A solid-state battery comprising a cathode unit according to any one of claims 1 to 9.

11. A method for manufacturing a cathode unit for a solid-state battery, comprising the steps of: A powder mixture is produced from an electrode material, a solid electrolyte material, a conductive additive, and polytetrafluoroethylene as a binder, the powder mixture comprising less than 1 weight percent polytetrafluoroethylene; and at least partially fibrillated polytetrafluoroethylene is formed in the powder mixture by the action of shear forces on the powder mixture; The powder mixture is then formed into a flexible composite layer in a method of manufacturing the cathode unit.

12. The formation of the at least partially fibrillated polytetrafluoroethylene is carried out by grinding, mixing with a worm shaft or calendar roll device, a kneading device, a mortar device, or a combination thereof. A method for producing a cathode unit according to claim 11.

13. The forming of the powder mixture into the flexible composite layer is carried out by rolling, pressing or extrusion. A method for producing a cathode unit according to claim 11 or 12.

14. The application of the flexible composite layer to the current collector layer is carried out at a temperature ranging from 60° C. to 120° C. A method for producing a cathode unit according to any one of claims 11 to 13.

Citation Information

Patent Citations

  • Application of sulfide electrolyte in preparing all-solid-state battery

    CN105489931A

  • Nonaqueous electric double layer capacitor and method of producing cell using the same

    JP1999329904A

  • Positive electrode for all-solid lithium battery and method for manufacturing the same, and all-solid lithium battery

    JP2012099315A

  • Negative electrode body and lithium ion battery

    JP2012164571A

  • Lithium ion secondary battery and method for producing positive electrode active material for lithium ion secondary battery

    JP2013089321A